Does managerial behavior of managing earnings mitigate the relationship between corporate governance and firm value? Evidence from an emerging market - Mian Sajid Nazir; Talat Afza (Future Business Journal, 2018)
The relationship between corporate governance and managerial choices for value creation is a topic of continuing interest for researchers. One of most significant managerial decisions that affect value is Discretionary Earnings Management (DEM) which is the judgmental adjustments in firm's reported accounting earnings by managers to upsurge firm value temporarily. Effective corporate governance structure to control this opportunistic behavior of mangers can presumably make accounting earnings more reliable and more informative for the stakeholders and hence, increase firm value. Based on 1944 firm year observations for listed firms in Pakistan, this study aims at to analyze the role of corporate governance in enhancing firm value along with the moderating role of DEM using models proposed by Kasznik (1999) and Beatty, Ke, & Petroni (2002) for detecting earnings management practices of managers. The results report that corporate governance significantly and positively influences firm value confirming the positive role of corporate governance in mitigating agency problem and enhancing the firm value. Moreover, corporate governance mechanisms may mitigate the managers' opportunistic behavior of manipulating the reported earnings. Furthermore, the results report that the behavior of managers is opportunistic towards managing earnings and they are destroying the current and subsequent firm value by manipulating the reported accounting earning. Finally, this opportunistic behavior of managers to manipulate earnings is negatively moderating the well-established positive relationship of corporate governance and firm value.
Keywords: 650; Corporate governance; Discretionary earnings management; Firm value; Kasznik model; Moderating effect; Opportunistic behavior